The Just War Doctrine: Has the Catholic Church Abandoned It? - Bernardo, Henry L. (Technium Social Sciences Journal, 2021)
One of the issues being discussed heatedly within the Catholic Church nowadays particularly due to Pope Francis’ recent encyclical letter Fratelli Tutti, is the just war doctrine. In his encyclical letter, the pope seems to suggest a change or discontinuance of the Catholic Church’s just war doctrine. Thus, the question that people ask is: Has the Catholic Church changed her official teaching and has finally abandoned or has moved away from the just war doctrine? This paper sheds light on this issue and argues that the Catholic Church has not changed the just war doctrine and it is still part of the official teaching of the Catholic Church. It further argues that the teaching on just war and loving our neighbor, including our enemies, are parts of one and the same doctrine. What appears to be a change of doctrine is simply a change in emphasis. The current prevailing opinion in the Church simply emphasizes one side in the continuum of the Church’s teaching on loving one’s neighbor and making peace, justice, and common good prevail in the whole world.